FEATURES OF ACTUALIZATION OF THE MEANINGS OF FORMAL AND TAUTOLOGICAL EXPRESSIONS IN DIALECTAL DISCOURSE - Golianych, Maria (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2024)
Abstract. The article explores the peculiarities of actualization the meanings of such formally tautological expressions as cholovyík ye cholovík, zhýnka ye zhýnka, dytýna ye dytýna, zhytié ye zhytié, which function in the residents speech of the village of Tyudiv; it is shown how the given language formulas, included in addressee-adressor relationships, acquire different emotive-evaluative and communicative-pragmatic meanings; it is proved that the semantic content of these statements depends on the communication situation and is formed by units of different language levels.